Technical feasibility of the use of copper slag as sand replacement in mortars of masonry walls - Pradena-Miquel, Mauricio (2019)
Chile is one of the largest generators of copper slags (CS) worldwide with around 50 million tons accumulated. As the CS have similar physicochemical characteristics to the raw materials of cement, their application in the production of sustainable mortars for use in masonry walls is very attractive. The objective of the present article is to study the technical feasibility of the use of CS as sand replacement in cement mortars of masonry walls. For that, their properties and characteristics are compared in laboratory with a standard mortar (without CS). Different properties of the cement mortar are analyzed, such as consistency, density, flexural and compressive strength, and adhesive strength. Moreover, its influence on the compressive and shear strength of confined masonry elements is also analyzed. The results show that the incorporation of CS in masonry mortars has a positive influence, increasing the adhesive strength (20.2%), compressive strength (18.1%) and shear strength (12%). Therefore, for the conditions analyzed, the use of cement mortars with CS in confined masonry walls is technically feasible.